The Role and Influence of Malaysia in ASEAN and the Regional Impact of the Organization on the Nation - Mahaseth, Harsh; Hilali, Sabrina (Asian Journal of International Affairs, 2021)
ASEAN and Malaysia, have successfully wielded each other’s existence to accomplish success in various aspects. Malaysia has played a crucial role in facilitating and molding the overall development and progress of ASEAN and played a vital part in establishing the foundation of the ASEAN Charter which presents the lawful character of ASEAN. On the other hand, Malaysia is a trading country that strongly relies on its associates at the international stage and ASEAN comes on the way of uplifting the process. Malaysia has received various advantages of trade incentives, international relations, and facilities like investment coordination, trade liberalization, etc. This paper intends to manifest the influence of ASEAN in Malaysia. It also highlights profuse aspects of the role of Malaysia on ASEAN, how they build each other’s strength. The purpose of this paper is to bring the issue to light about how ASEAN can overcome the shortcomings and depend on its intrinsic unity only, and create a stronger relationship with Malaysia by overcoming the deficiencies.